2015
DOI: 10.1371/journal.pone.0138019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diet-Induced Obesity and Testosterone Deficiency on the Cardiovascular System: A Novel Rodent Model Representative of Males with Testosterone-Deficient Metabolic Syndrome (TDMetS)

Abstract: IntroductionCurrent models of obesity utilise normogonadic animals and neglect the strong relationships between obesity-associated metabolic syndrome (MetS) and male testosterone deficiency (TD). The joint presentation of these conditions has complex implications for the cardiovascular system that are not well understood. We have characterised and investigated three models in male rats: one of diet-induced obesity with the MetS; a second using orchiectomised rats mimicking TD; and a third combining MetS with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 97 publications
(108 reference statements)
1
12
1
Order By: Relevance
“…As we have demonstrated previously with similar models (35,46), we propose that the HF/HSϩORX model used in the present study is an appropriate representation of males with TEST-deficient MetS.…”
Section: Characteristics Of the Test-deficient Mets Modelsupporting
confidence: 65%
“…As we have demonstrated previously with similar models (35,46), we propose that the HF/HSϩORX model used in the present study is an appropriate representation of males with TEST-deficient MetS.…”
Section: Characteristics Of the Test-deficient Mets Modelsupporting
confidence: 65%
“…Donner and colleagues reported that the rats fed with the obesogenic diet for 28 weeks had a similar level of serum testosterone level as the control rats (Donner et al 2015), whereas Silva and colleagues reported that HFD feeding for 30 weeks effectively reduced plasma testosterone levels in obese rats, compared with lean rats (Silva et al 2015). Our data indicated that testosterone deprivation did not affect peripheral insulin-resistant status, but it led to a reduction in both body weight and visceral fat weight.…”
Section: Journal Of Endocrinologymentioning
confidence: 99%
“…Our previous study using obese insulin-resistant rats demonstrated that testosterone deprivation at a very young age followed by long-term consumption of a high-fat diet (HFD) could accelerate but not aggravate LV dysfunction [4]. A recent study showed that obese insulin-resistant rats subjected to testos terone deprivation in middle age had an exacerbated insulin-resistant condition as indicated by increased HOMA-IR [12]. In addition, LV mass was also reduced and serum CK-MB levels were increased in testosterone-deprived obese insulin-resistant rats subjected to myocardial ischemia reperfusion injury [13].…”
Section: Introductionmentioning
confidence: 99%